Numerical Simulation of Pipeline Deformation Caused by Rockfall Impact. (13th May 2014) - Zhang, Jie; Liang, Zheng; Han, Chuanjun
Abstract : Rockfall impact is one of the fatal hazards in pipeline transportation of oil and gas. The deformation of oil and gas pipeline caused by rockfall impact was investigated using the finite element method in this paper. Pipeline deformations under radial impact, longitudinal inclined impact, transverse inclined impact, and lateral eccentric impact of spherical and cube rockfalls were discussed, respectively. The effects of impact angle and eccentricity on the plastic strain of pipeline were analyzed. The results show that the crater depth on pipeline caused by spherical rockfall impact is deeper than by cube rockfall impact with the same volume. In the inclined impact condition, the maximum plastic strain of crater caused by spherical rockfall impact appears when incidence angle α is 45 ° . The pipeline is prone to rupture under the cube rockfall impact when α is small. The plastic strain distribution of impact crater is more uneven with the increasing of impact angle. In the eccentric impact condition, plastic strain zone of pipeline decreases with the increasing of eccentricity k .